National Survey of Research and Development(R&D)2012 - Mohd. Asraf, Ratnawati; Tunku Ahmad, Tunku Badariah (MASTIC, MOSTI, 2012)
This is a technical report that presents the highlights of Malaysia's R&D activities and expenditure over a 3-year period (2010-2012).